Expenditure trends in ambulatory care sensitive conditions in Piauí, Brazil, 2009 a 2018. (30th September 2020) - Sousa, R; Silva, F; Silva, R; Santos, R; Justino, A; Cardoso, T; Cardoso, O
Abstract: Introduction: Hospitalizations for ambulatory care sensitive conditions (ACSC) are an indicator that assesses the effectiveness of Primary Health Care. Such hospitalizations burden the public health budget and use the resources that could subsidize other health actions. Aim: Analyze expenditure trends in hospitalizations for Ambulatory Care Sensitive Conditions (ACSC) in Piauí, Brazil, from 2009 to 2018. Methods: Ecological time-series study based on data from the Hospital Information System (SIH). For temporal trend analysis, a linear regression model was built using the Stata version 14 program. Results: US 119, 559, 009.56 (Average = US 6, 292, 579.45/year) was spent on ACSC, representing 17.3% of the total hospitalizations (US 690, 714, 037.24). 2010 was the period with the highest cost (14.8%). In contrast, 2018 was the year with the lowest expenditure (5.8%). 23.7% of the costs went to hospitalizations for gastroenteritis. There was a significant decrease in total expenses with ACSC (β = -1.27; 95%CI: -1.65; -0.89; p < 0.001). There was also a reduction in expenses per individual hospitalized, while in 2009, the average expenditure was US 230.97/hospitalization, in 2018 it was US 157.30/ hospitalization, representing a significant reduction of 31.9%, (β = -12.4; 95%CI: -18.2; -6.6; p = 0.001). The "asthma" and "hypertension" groups showed the greatest cost reductions, 84.8% and 80.7%, respectively. However, an increase in spending on diseases related to prenatal and childbirth (4.1 times) and skin infection (3.9 times) was identified. Conclusions: Part of the cost reduction is explained by the reduction of hospitalizations for ACSC. The reduced spending averages are compatible with lower hospitalizations by most expensive groups. Linked to these findings, it is observed that Brazil has faced a period of recession since 2015. To this end, additional research must be carried out to relate the expansion of health coverage with the results presented. Key messages: The costs of hospitalizations for PHC-sensitive conditions reflect the policy of inducing health system coverage, being lower for greater coverage. The evaluation of the cost of specific groups allows the induction of PHC policies focusing on the specific care for each group with a higher cost so as not to burden the health system.